The Autobiography: Narrative Model of Picaresque Novel in La colina del buey (1972), by José León Sánchez - Chavarría Castro, Baruc (2020)
The novel Picahueso (1971), the second one written by José León Sánchez and later titled La colina del buey (1972), has been associated with the narrative model of Spanish picaresque. This aspect, however, has not been studied in detail. The structural characteristics determined by the theory about the picaresque genre are recognizable in J. L. Sánchez's narrative, among them the most important one: autobiography. Based on this fundamental characteristic, it is proposed to study how the vital material of the protagonist, Manuel Miranda Miranda, aka Picahueso, is written. Although the usefulness of structural concepts present in the story is recognized, the approach to the novel is methodologically comparative. It is considered that the autobiographical is handled in a different way, turning the writing of the self into the writing of the other; into an otobiography.